Cover Picture: Selenium–Selenium Bond Cleavage of Diaryl Diselenide Radical Anions During Pulse Radiolysis (ChemPlusChem 1/2015). Issue 1 (25th November 2014) - Tojo, Sachiko; Fujitsuka, Mamoru; Ouchi, Akihiko; Majima, Tetsuro
Abstract : The cover picture shows the mechanism of Se–Se σ‐bond cleavage of the di‐α‐naphthyl diselenide radical anion (orange) to form an α‐naphthylselenyl radical (dark blue) and an α‐naphthylselenyl anion based on the transient absorption spectroscopic change during pulse radiolysis. An unpaired electron is initially localized in the σ* orbital of an elongated Se–Se σ‐bond (orange), and then delocalized over two naphthalene rings and Se–Se bond (green) as a result of the interaction between two naphthalene π* orbitals and a Se–Se σ* orbital. Details are given in the Full Paper by Tetsuro Majima et al. on page 68 .